(untitled) (GEON Journal (Management, Organizations and Business), 2025)
Problematic. One of the most significant challenges facing an organization dedicated to offering lodging services—and whose vision is to be among the best in its category—is the development of a human capital management model aimed at increasing the efficiency and effectiveness of its personnel. Objectives. To identify documented cases of human capital management in tourism companies within both national and international contexts. Materials and methods. The methodology used in this study is a documentary review of scientific articles, qualitatively describing cases related to human capital management in the tourism sector. Results. The results highlight the various situations that must be considered in managing human capital within a five-star hotel, in order to effectively manage organizational talent. Discussion. To build a functional workforce, the hotel must implement a human capital management model that includes clear procedures, standards, and policies for recruitment, selection, hiring, training, performance evaluation, and incentive systems. These elements are essential for achieving sustainable development and improving the overall quality of human capital. Conclusions. The study concludes that if hotel management adopts and responsibly applies a human talent management model—along with its associated processes, policies, standards, and strategies—the quality of recruited talent will improve, leading to more efficient and effective organizational processes.